PENGARUH KECERDASAN EMOSIONAL, MOTIVASI KERJA, DAN SIKAP KERJA TERHADAP KINERJA KARYAWAN PADA PT ITHACA RESOURCES - Mochammad Subagio (Jurnal Manajemen., 2015)
The obyective of this research is to study the effect of emotional intelligence,job attitudes, work motivation on performance employee. The research was conducted at the Ithaca Resources Company Jakarta. It was using causal study method. The samples of this research were 90 personel of the Ithaca Resources Company that selected randomly. The research findings are: (1) there is a direct effect of emotional intelligence on job attitudes (2) there is a direct effect of work motivation on job attitudes (3) there is a direct effect of emotional intelligence on performance employee; (4) there is a direct effect of work motivation on performance employee; (5) there is a direct effect of job attitudes on performance employee; Based on these findings, it could be concluded that performance employee is affected by emotional intelligence, work motivation and job attitudes. And the emotional intelligence is the most dominant that effect the performance employee. On the other word, the higher emotional intelligence effects more directly on the performance employee Therefore, the emotional intelligence, work motivation and job attitudes should be taken into consideration in determining performance employee at ithaca resouces company of jakarta